2020
DOI: 10.1089/vio.2019.0051
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Differences Among Sexual Offenders: A Targeted Review with Limitations and Implications for Future Directions

Abstract: As sexual assault and child sexual abuse continue to be worldwide public health concerns, research has continued to explore factors associated with sexual offending. Structural and functional neuroanatomical brain differences have been examined in an effort to differentiate sexual offenders and their behavior. This targeted review searched PubMed and Google Scholar for empirical studies using brain imaging techniques to examine possible structural or functional differences among control groups compared with at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…Siep et al (2019) found that violent offenders showed an altered pattern of amygdala connectivity (as revealed by resting state scans) before and after generating emotions of anger and happiness. Other studies with this type of population (Kirk-Provencher et al, 2020) have found that those convicted of rape and other sexual crimes show reduced gray matter in areas such as the amygdala, insula, and dlPFC, along with a different pattern of brain functioning, as shown, for example, by hyperactivation of the amygdala in the presence of inappropriate stimuli. Finally, it seems that having suffered traumatic experiences of violence in childhood impairs the mechanisms necessary for making moral decisions, including emotions, empathy, cognition, and inhibitory control.…”
Section: Introductionmentioning
confidence: 79%
“…Siep et al (2019) found that violent offenders showed an altered pattern of amygdala connectivity (as revealed by resting state scans) before and after generating emotions of anger and happiness. Other studies with this type of population (Kirk-Provencher et al, 2020) have found that those convicted of rape and other sexual crimes show reduced gray matter in areas such as the amygdala, insula, and dlPFC, along with a different pattern of brain functioning, as shown, for example, by hyperactivation of the amygdala in the presence of inappropriate stimuli. Finally, it seems that having suffered traumatic experiences of violence in childhood impairs the mechanisms necessary for making moral decisions, including emotions, empathy, cognition, and inhibitory control.…”
Section: Introductionmentioning
confidence: 79%
“…In line with the finding of some reinforcement learning impairments in the control group of individuals convicted of nonsexual violent offenses, fronto-limbic abnormalities have also been reported in populations that consist of individuals convicted of nonsexual violent offenses (e.g., individuals with violent offenses and a diagnosis of psychopathy and individuals with violent offenses and a diagnosis of antisocial personality disorder: Motzkin et al, 2011;Völlm et al, 2004). This indicates that such abnormalities should probably be seen as neurobiological correlates of violent offending behavior in general rather than as being specific to sexual offending behavior (Kirk-Provencher et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Whereas purely cognitive executive dysfunctions reflect a disruption of dorsolateral and ventrolateral prefrontal cortical function, dysfunctional emotion and motivated-rela ted cognitive processes in general and reinforcement learning impairments in particular involve dysfunction of ventromedial pathways that connect the mesolimbic reward struc tures (e.g., the amygdala and the insula) to ventromedial prefrontal and orbitofrontal cortical areas of the brain (Jonker et al, 2015;Kelley et al, 2019;Kelley et al, 2015;Salehinejad et al, 2021;Schuck et al, 2018;Wagner & Heatherton, 2016). Several magnet ic resonance imaging (MRI) studies indeed reported structural and functional abnormali ties in limbic and prefrontal structures including the amygdala and the orbitofrontal cor tex in ISOCs (Jordan et al, 2020;Kirk-Provencher et al, 2020;Mohnke et al, 2014). Two recent functional imaging studies, moreover, revealed diminished resting state functional connectivity between limbic structures (especially the amygdala) and prefrontal cortical areas (including the dorsolateral prefrontal cortex and the orbitofrontal cortex extending to the anterior cingulate cortex) in nonpedophilic ISOCs relative to nonoffender controls (Kärgel et al, 2015) and in pedophilic ISOCs relative to nonoffending individuals with pedophilic preferences and nonoffender controls (Kneer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study suggest that individuals with ID may constitute a significant proportion of those incarcerated for sexual offenses against adults. Those who offend against adults differ from those who offend against children in terms of psychological characteristics (Shechory & Ben-David, 2005;Sigre-Leirós et al, 2014), and neuroimaging research has hinted at brain differences between these groups (Joyal et al, 2007;Kirk-Provencher et al, 2020). While some studies have examined the neurodevelopmental origins of pedophilic preference among those with ID (Blanchard et al, 2002(Blanchard et al, , 2003, more research is needed to understand the role that brain development may play in sexual offending against adults.…”
Section: Implications and Future Directionsmentioning
confidence: 99%